Copy number load predicts outcome of metastatic colorectal cancer patients receiving bevacizumab combination therapy. Issue 1 (December 2018) - Smeets, Dominiek; Miller, Ian; O'Connor, Darran; Das, Sudipto; Moran, Bruce; Boeckx, Bram; Gaiser, Timo; Betge, Johannes; Barat, Ana; Klinger, Rut; Grieken, Nicole; Cremolini, Chiara; et al.
Abstract Increased copy number alterations (CNAs) indicative of chromosomal instability (CIN) have been associated with poor cancer outcome. Here, we study CNAs as potential biomarkers of bevacizumab (BVZ) response in metastatic colorectal cancer (mCRC). We cluster 409 mCRCs in three subclusters characterized by different degrees of CIN. Tumors belonging to intermediate-to-high instability clusters have improved outcome following chemotherapy plus BVZ versus chemotherapy alone. In contrast, low instability tumors, which amongst others consist ofPOLE -mutated and microsatellite-instable tumors, derive no further benefit from BVZ. This is confirmed in 81 mCRC tumors from the phase 2 MoMa study involving BVZ. CNA clusters overlap with CRC consensus molecular subtypes (CMS); CMS2/4 xenografts correspond to intermediate-to-high instability clusters and respond to FOLFOX chemotherapy plus mouse avastin (B20), while CMS1/3 xenografts match with low instability clusters and fail to respond. Overall, we identify copy number load as a novel potential predictive biomarker of BVZ combination therapy. Increased copy number alterations, indicative of chromosomal instability, is associated with poor cancer outcome. Here, metastatic colorectal cancer patients displaying intermediate-high CIN associate with improved outcome following chemotherapy and bevacizumab treatment, suggesting CIN as a predictive biomarker.